The Effectiveness of Scrabble Games to Promote Vocabulary Achievement of Migrant Workers’ Children in Malaysia - Jonanda Wahyu Mahendra; Ana Maghfiroh; Bambang Harmanto; Dwi Hatmoko (Universitas Pendidikan Mandalika, 2024)
Vocabulary skill is crucial for every English as foreign language (EFL) learners as it forms the foundation for effective communication, comprehension, and overall language proficiency. However, Indonesian migrant workers’ children who attend school at PPWNI Klang that has only two teachers who are not experts in the field of English, resulting in a lack of enthusiasm among students to learn the language. The study aimed to examine whether the use of Scrabble games was effective in increasing students' vocabulary achievement or not. The research design was a pre-experimental research design, with one group pretest-posttest used by the researchers. The sample of the study was 21 students of grade 9 SMP PPWNI Klang Malaysia, selected using purposive sampling. The results of the pretest and posttest data were analyzed using the paired sample t-test through the SPSS software. The findings of the study showed that Sig. (2-tailed) of 0.000 < 0.05. This means that there is a significant difference and effectiveness in learning outcomes after using the scrabble games method in learning English vocabulary. As the conclusion, a scrabble game is an effective strategy for teaching vocabulary especially to students facing various challenges, such as limited teacher resources and an unsupportive learning environment, they can be comfortable and motivated to continue learning due to the enjoyable game-based learning experience.